Feasibility on accurate measurement of non-uniform strain field through contact methods - Pratyush Kumar (Elsevier, 2021)
When straight material filaments do not remain straight after deformation, the strain varies spatially. These spatially varying strain fields arise because of (1) non-uniform distribution of boundary traction, (2) presence of residual stress in the reference configuration, (3) the body being inhomogeneous. The strain measured using devices such as extensometer and strain gauge assumes that the strain is uniform over the gauge length, irrespective of the strains actual variation. Here the accuracy of the strain estimated using contact strain measurement techniques is investigated by assuming that the uniaxial strain (not stress) varies periodically along the measurement axis. A tight bound for the error in the measured strain is obtained and verified through numerical simulation. This study’s significant finding is that for gauge length of strain measurement about two times the periodicity of the strain variation, the measured strain’s value would be repeatable but with a significant error. Thus, one has to be cautious about the magnitude of the estimated non-uniform strain.